Biological effects of socio-economic changes in the rural environment of the Krosno province in 1967–1997 - Łaska-Mierzejewska, Teresa (Anthropological Review, 1997)
Village girls in the age of 9-18 , inhabiting Krosno region, were surveyed in 1967 (n=l 134), 1977 (n=1028), 1987 (n=l 255), and 1997 (n=1992). Based on the source of income of the families, three groups were separated: farmers, farmers-workers and nonfarmers. The girls were also divided on the basis of the number of children in the family, and the educational status of their fathers and mathers. The age at menarche for entire region was 13.94 ± 0.06 in 1967, and 13.38 ± 0.05 in 1997. During the period of 30 years the acceleration of maturation was 0.54 of a year. This result does not reflect the real socioeconomic situation inside the rural population. In the period 1977-1997 the deceleration of menarcheal age was registered in nonfarmers group, in the group of families with 5 and more children, and in the group of girls with the highest level of fathers education. In 1977 the menarcheal age of girls from farmer group was 14.01 ± 0.21 and from nonfarmer group – 13.03 ± 0.12; in 1997 those ages were 13.52 and 13.39 respectively. The differences between compared groups changed, from 0.98 in 1977 to 0.13 of a year in 1997, as a result of socioeconomic situation in the decades 1977-1987 and 1987-1997.